(untitled) - Parlakorn Kornpitack; Sudaporn Sawmong (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study empirically tested the model to evaluate the factors that affect the use of learning English with Virtual School OnlinePlatform among Thai High School students. The study explored the behavioral intention and actual use of online learning platform from the perspective of High school students, applying the UTAUT model, with addition to the previous education success construct. The study was cross-sectional from the data corrected from 1,044 respondents. The analysis was conducted using structural equation modeling. The results revealed that: (1) behavioral intention (BI) was positively and significantly influenced by performance expectancy, social influence, facilitating conditions, and previous education success; (2) actual use was found to be positively, and significantly influenced by behavioral intention to use; (3) the actual use was found to be positively and significantly influenced indirectly through behavioral intention by performance expectancy, social influence, facilitating conditions, and previous education performance; (4) effort expectancy was found to have a negative non-significant influence on behavioral intention, and indirectly on actual use. The findings are relevant towards the policy makers in the Thailand education system, as they make effort towards improving the English education learning among high school students.